Fracture rate and time to fracture in dogs with appendicular osteosarcoma receiving finely fractionated compared to coarsely fractionated radiation therapy: A single institution study - Carissa J. Norquest; Charles A. Maitz; Deborah A. Keys; Melanie Moore; Jeffrey N. Bryan; Tara J. Ehling; Jimmy C. Lattimer; Brian K. Flesner (Veterinary Medicine and Science, 2022)
Abstract Background Radiation therapy (RT) is used for local pain alleviation in dogs with appendicular osteosarcoma (OS), especially among dogs that are poor surgical candidates for amputation. However, many historical reports of fractionated protocols lack time to fracture and fracture rates. Objectives The primary objectives of this retrospective study were to determine fracture rate and time to fracture of dogs receiving RT (coarse or fine fractionated) for appendicular OS. Secondary objectives were to evaluate tolerability and disease outcome measures. Methods Fifty‐one dogs that received RT as part of treatment for appendicular OS were available for evaluation. Forty‐five received coarse fractionation (C‐RT, 8 or 6 Gy per fraction protocols [C‐RT8 or C‐RT6]) while the remaining six received fine fractionation (F‐RT). Results The overall pathologic fracture rate was 37%. Pathologic fracture rate was significantly higher for dogs that received F‐RT (5/6, 83%) compared to dogs that received C‐RT (12/40, 30%, p = 0.021). In the 17 dogs that fractured, the overall median time to fracture was 57 days. For all dogs, the median progression free interval (PFI) and median overall survival time (OST) were 90 and 140 days, respectively. In a very small cohort of dogs (n = 7) treated with zoledronate and RT, fracture rate was 0% and extended survival times were noted. Conclusions In conclusion, C‐RT is recommended over F‐RT due to lower risk of pathologic fracture and similar PFI. Prospective evaluation of combined C‐RT and zoledronate, especially for dogs with poor surgical candidacy, is warranted for the treatment of canine appendicular osteosarcoma.